Percutaneous Ethanol Sclerotherapy for Recurrent Adventitial Cystic Disease of External Iliac Vein after Surgical Treatment: A Case Report - Ann, Jun Hyung; Kim, Jeong Ho; Byun, Sung Su; Kang, Jin Mo; Kim, Hyung Sik; Choi, Hye Young (Journal of the Korean Society of Radiology, 2015)
Adventitial cystic disease (ACD) is a rare, but well-characterized vascular disease. It is most commonly seen in the popliteal artery, but it has also been reported in the venous system. The most commonly involved segment has been the common femoral vein; the disease resulted in luminal compromise and extremity swelling. We report here on a case of percutaneous aspiration and ethanol sclerotherapy for recurrent ACD after surgery of the external iliac vein in a 70-year-old man who presented with a painless swelling of his left leg. KCI Citation Count: 1